Activation of TREK-1, but Not TREK-2, Channel by Mood Stabilizers - Kim, Eun-Jin (Int J Mol Sci, 2017)
Earlier studies have demonstrated that the tandem pore domain weak inward rectifying K(+) channel (TWIK)-related K(+) (TREK)-1 channel is inhibited by antidepressants and is associated with major depression. However, little is known about the effect of mood stabilizers that are commonly used for treatment of bipolar disorder on TREK channels, members of the two-pore domain K(+) (K(2P)) channel family. This study sought to investigate the effect of mood stabilizers on TREK-1 and TREK-2 channels. HEK-293A cells were transfected with human TREK-1 or TREK-2 DNA. The effect of mood stabilizers on TREK-1 and TREK-2 was studied using the patch clamp technique. Changes in TREK protein expression by mood stabilizers were studied in the HT-22 mouse hippocampal neuronal cells using western blot analysis. Lithium chloride (LiCl, 1 mM), gabapentin (100 μM), valproate (100 μM), and carbamazepine (100 μM) increased TREK-1 currents by 31 ± 14%, 25 ± 11%, 28 ± 12%, and 72 ± 12%, respectively, whereas they had no effect on TREK-2 channel activity. In addition, western blot analysis showed LiCl and carbamazepine slightly upregulated TREK-1 expression, but not TREK-2 in the HT-22 cells. These results suggest that TREK-1 could be a potential therapeutic target for treatment of bipolar disorders as well as depression, while TREK-2 is a target well suited for treatment of major depression.